3D Research Challenges in Cultural Heritage VI: DigitalTwin versus MemoryTwin - (:unkn) unknown (My University, 2025)
This book presents a collection of papers focussing on 3D digitisation in the domain of cultural heritage. The use of data acquisition technologies in digitising cultural heritage holds great potential for preserving and disseminating the history of mankind. However, to exploit these opportunities in full, comprehensive guidelines for documenting the process of digitisation are required. Only then can the efficiency and credibility of digital representations be assured.
Keywords: Digital Heritage 3D Reconstruction; Metadata; Paradata; Digital Twin; MemoryTwin; Cultural Heritage